Use of lung ultrasound in school-aged children with wheezing - Marina Attanasi; Simone Sferrazza Papa; Annamaria Porreca; Giuseppe F. Sferrazza Papa; Giuseppe F. Sferrazza Papa; Paola Di Filippo; Francesca Piloni; Giulia Dodi; Francesco Sansone; Sabrina Di Pillo; Francesco Chiarelli (Frontiers Media S.A., 2023)
BackgroundThere is limited information available on fast and safe bedside tools that could help clinicians establish whether the pathological process underlying cases of wheezing is due to asthmatic exacerbation, asthmatic bronchitis, or pneumonia. The study's aim was to characterize Lung Ultrasound (LUS) in school-aged children with wheezing and evaluate its use for their follow-up treatment.Materials and methodsWe carried out a cross-sectional study involving 68 consecutive outpatients (mean age 9.9 years) with wheezing and suggestive signs of an acute respiratory infection. An expert sonographer, blinded to all subject characteristics, clinical course, and the study pediatrician's diagnosis, performed an LUS after spirometry and before BDT. The severity of acute respiratory symptoms was determined using the Pediatric Respiratory Assessment Measure (PRAM) score.ResultsThe LUS was positive in 38.2% (26/68) of patients [12 (46.1%) with multiple B-lines, 24 (92.3%) with consolidation, and 22 (84.6%) with pleural abnormalities]. In patients with pneumonia, asthmatic bronchitis, and asthma, the percentages of those patients with a positive LUS were 100%, 57.7%, and 0%, respectively. Of note, patients with a positive LUS were associated with an increased need for hospital admission (30.8% vs. 2.4%, p = 0.001), administration of oxygen therapy (14.6% vs. 0%, p = 0.009), oral corticosteroids (84.6% vs. 19.0%, p < 0.001), and antibiotics (88.5% vs. 11.9%, p < 0.001); and a higher median value of PRAM score (4.0 (2.0-7.0) vs. 2.0 (1.0-5.0); p < 0.001).ConclusionsOur findings would suggest the use of LUS as a safe and cheap tool used by clinicians to define the diagnosis of school-aged children with wheezing of unknown causes.